Islamism in Indonesia : Politics in the Emerging Democracy - Platzdasch, Bernhard (Book collections on Project MUSE., 2009)
The fall of President Soeharto in May 1998 and the introduction of multi-party democracy by President BJ Habibie have unleashed religious parties (both Islamic and Christian) in Indonesian politics. This study shows that the Islamist agenda of the Islamist parties is overshadowed by their political pragmatism. This book is a must-read account on the rise and failure of the Islamist struggle in Indonesia's emerging democracy. Platzdasch's work is without a doubt a significant and timely contri ...